Weight training - Pre-adolescent strength training - Just do it! - Sibte, N.
In former times resistance or weight training (as opposed to the disciplines of weightlifting or power-lifting) has not been recommended for pre-adolescents because of the concerns for injury and the questionable efficacy of this type of training to improve strength. In this article author puts an end to the myths and looks at the facts about strength training for pre-adoleszents.